ANALlSIS PINDAH PANAS PADA PENDINGINAN DALAM TANAH UNTUK SISTEM HIDROPONIK - Herry Suhardiyanto; Muhammad Maftuh Fuadi; Yeni Widaningrum (PERTETA, 2007)
ABSTRACTZone cooling is used in greenhouses to maintain the area surrounding the plants at a level of temperature that is not too high and can be tolerated by the plants, even though air temperature inside the greenhouse rises some degrees above the temperetute level of outside air. Cooling the root zone by distributing the cooled nutrient solution is one of the most effective methods of zone cooling. In this experiment, ground environment with a relatively low temperature has been used to reduce the temperature of nutrient solution by placing trio nulriont solution tank in ebout 7 m depth under the ground (surface) It has been shown that tne method was efficient in energy use, because It need only energy for pumping the water from the depth to the floor level through a vertical pipe. Temperature of nutrient solution flowing out from the emitter with the tank placed under the ground (surface) could be maintained 0.1 to 1.9 °C lower than that sourced from tank placed at floor level. A heat transfer model has been developed to prodict the nutrient solution temperature flowing out from the vertical pipe. It has been shown that the predicted temperature of nutrient solution agreed well with that of the measured temperatures. Keywords: drip Irrigation system, heat transfer analysis, ground cooling. Diterima: 11 Agustus 2007; Disetujui: 3 Nopember 2007